"Below the wood behind Lety, a concentration camp was set up". Analysis of unknown photographs and a typescript by Karel Hungr from Mirovice - Berkyová, Renata (Romano džaniben, 2022)
The text analyses six photographs and one typescript linked with the history and post-war perception of the site of the former concentration camp in Lety u Písku that are part of the photographic collection "Mirovice region and the Protectorate Period in Photography (1939-1945)" by Karel Hungr, an amateur photographer from Mirovice. The text deals not only with the reconstruction of the situations depicted or hinted at in the archival materials, but also with Hungr´s motivations when taking the pictures during the Second World War and when creating the accompanying texts at the end of 1960. The text thus explores what can be learned from the documents for further research on the post-war perception of the Holocaust of the Czech Roma and Sinti.